2022
DOI: 10.3390/cancers14153774
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Approaches to HER2-Low Breast Cancer: Current Practice and Future Directions

Abstract: HER2-low breast cancer (BC) has a poor prognosis, making the development of more suitable treatment an unmet clinical need. While chemotherapy is the main method of treatment for HER2-low BC, not all patients benefit from it. Antineoplastic therapy without chemotherapy has shown promise in clinical trials and is being explored further. As quantitative detection techniques become more advanced, they assist in better defining the expression level of HER2 and in guiding the development of targeted therapies, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 164 publications
0
6
0
Order By: Relevance
“…To characterize this cohort with stage I TNBC tumors, we evaluated patient DFS, OS, and background (age, tumor size, NG, HER2/ER/PgR status, surgical procedure, and whether adjuvant radiotherapy or chemotherapy was administered). Among these breast cancer-related factors, HER2 1+, 2+, and ISH negative were termed HER2-low, which has been reported to have different characteristics from the HER2-0 group ( 18 ). Therefore, we focused on HER2-low, which is present in some TNBC cases, as a breast cancer-related factor affecting recurrence risk and treatment choice for patients with TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…To characterize this cohort with stage I TNBC tumors, we evaluated patient DFS, OS, and background (age, tumor size, NG, HER2/ER/PgR status, surgical procedure, and whether adjuvant radiotherapy or chemotherapy was administered). Among these breast cancer-related factors, HER2 1+, 2+, and ISH negative were termed HER2-low, which has been reported to have different characteristics from the HER2-0 group ( 18 ). Therefore, we focused on HER2-low, which is present in some TNBC cases, as a breast cancer-related factor affecting recurrence risk and treatment choice for patients with TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…Initial HER2-targeted agents were ineffective against HER2low breast cancer (36). However, the ADC trastuzumab deruxtecan recently demonstrated efficacy in this setting (37).…”
Section: Breast Cancermentioning
confidence: 99%
“…Scholars have found that they can play a role in BC patients with HER2-low. 59,62,63 In addition, tri-specific antibodies are also gradually on the stage. Zheng et al 64 found that trispecific antibodies consisting of HER2, CD3, and CD28 arms can promote the regression of tumors with HER2 overexpression or low expression by stimulating CD4 T cells at a very low dose, which may provide the new drug development for the treatment of HER2-low/ zero BC.…”
Section: Treatment Of Targeting Her2 Receptorsmentioning
confidence: 99%
“…Zenocutuzumab is antibody‐dependent cell‐mediated cytotoxicity (ADCC)‐enhanced IgG antibody that targets HER2 and Her3 and blocks neuregulin signaling by preventing the formation of heterodimers. Scholars have found that they can play a role in BC patients with HER2‐low 59,62,63 . In addition, tri‐specific antibodies are also gradually on the stage.…”
Section: Treatment Of Her2‐low/zero Breast Cancermentioning
confidence: 99%